Effectiveness of Road Safety Education in Reducing Teenage Traffic Accidents: A Systematic Review - Francis Walugembe; Cua Ngoc Le; Hien Thi Nguyen; Sanhawat Chaiwong (My University, 2024)
Background: This systematic review examined the impact of road safety education (RSE) on reducing teenage traffic accidents and injuries in Southeast Asia on the basis of the literature. We evaluated the effectiveness of road safety education programs, contextual and cultural adaptations, the integration of practical training, implementation challenges, and the long-term impacts on teenage behavior. Materials and Methods: The study followed the guidelines of the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA). This involved counting the number of studies showing a positive, negative, or no effect. A search of the articles in the electronic databases PubMed, Scopus, and Google Scholar was conducted. The effectiveness of RSE was assessed by vote counting, tallying the number of studies showing positive, neutral, or negative impacts on teenage driving behaviour among those aged 13–19 years. A total of seventeen studies were selected for inclusion on the basis of predefined criteria. Results: When a systematic review was conducted, 17 key studies were identified for inclusion, reflecting diverse methodologies and focus areas. Research has shown that teenagers benefit significantly from receiving both theoretical knowledge and practical training. This comprehensive approach enhances their confidence and skills in adhering to traffic safety laws. Moreover, the involvement of parents and communities emerges as a vital factor for the success of educational initiatives. Conclusion: This study emphasizes the paramount importance of prioritizing long-term behavioural change and sustainability in road safety initiatives, particularly in teenagers. It advocates for a comprehensive approach involving community and parental engagement alongside educational programs. The findings emphasize the necessity for policymakers in Southeast Asia to allocate funding to culturally sensitive and standardized RSE programs, integrating practical training and long-term reinforcement strategies.
This manuscript, titled "Effectiveness of Road Safety Education in Reducing Teenage Traffic Accidents: A Systematic Review", presents a comprehensive analysis of existing research on the impact of road safety education programs on teenage traffic accident rates. Through a systematic review of relevant studies, the authors evaluate the effectiveness of various educational interventions aimed at improving road safety awareness among teenagers. The review synthesizes data from multiple sources to assess whether these programs lead to a measurable reduction in traffic accidents involving young drivers. The findings aim to inform policy decisions and guide the development of more effective road safety education strategies for reducing teenage traffic-related injuries and fatalities.
Keywords: Road Safety Education; Teenagers; Road Traffic Accidents; Southeast Asia